The Progress of Speech Production in People with Autism (Case Study on a Girl Named Aliya Salsabila Ramadhani) - Mubasyira, Mu’thia; Rafli, Zainal; Boeriswati, Endry (Future Science / FSH-PH Publications, 2021)
This study is titled the progress of speech production in people with autism (case study in a girl named Aliya Salsabila Ramadhani). The study was conducted by Mu'thia Mubasyira, Zainal Rafli and Endry Boeriswati. To correspond the email used is muthiamubasyira_9906921003@mhs.unj.ac.id and the orchid number is 0000-0002-4084-3382. This study was conducted with the aim to find out how the progress of speech production in people with autism with the object of research on a girl named Aliya Salsabila Ramadhani who is now 9 years old. This study tried to analyze the primary data obtained by explaining the progress of language and Aliya speech production from the age of 3 months old until now. This research uses descriptive qualitative methods that seek to describe the progress of Aliya language and speech production with a short narrative and exposure to data retrieval techniques used through observation of video documentation of activities carried out and through questionnaires and interviews. In addition, this study also uses relevant references as study materials so that holistic and thorough discussion results are obtained. From the characteristics that seem to be known that Aliya is classified as experiencing mild austism. It is also obtained through the analysis of language development and how Aliya interacts with the environment and the surrounding people. Aliya also has abstinence from certain foods to suppress so that her behavior is not too hyper or excessive. Aliya's language progress and speech production made significant increasement after she received developmental therapy and speech therapy and attended a special needs school. This research is expected to add to the treasures of science, especially those related to psycholinguistics with the study of language development and speech production in people with autism.